2017
DOI: 10.1002/we.2141
|View full text |Cite
|
Sign up to set email alerts
|

Bend‐bend‐twist vibrations of a wind turbine blade

Abstract: Dynamics of a wind turbine blade under bend-bend-twist coupled vibrations is investigated. The potential and kinetic energy expressions for a straight nonuniform blade are written in terms of beam parameters. Then, the energies are expressed in terms of modal coordinates by using the assumed mode method, and the equations of motion are found by applying Lagrange's formula.The bend-bend-twist equations are coupled with each other and have stiffness variations due to centrifugal effects and gravitational paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…[Gaonkar and Kulkarni, 2017] (91) ; [Warminski et al, 2021] (92) ; [Kloda et al, 2020] (93) ; [Guillot et al, 2020] (94) ; [Abdeljawad et al, 2020] (95) ; [Acar and Feeny, 2018] (96) https://www.indjst.org/ Most of the authors focused upon the design of controllers according to the accurate dynamic model of the flexible arm. Researchers used both the AMM and FEM to model the flexible arm without compromising the accuracy.…”
Section: Inertial Frame Of Referencementioning
confidence: 99%
“…[Gaonkar and Kulkarni, 2017] (91) ; [Warminski et al, 2021] (92) ; [Kloda et al, 2020] (93) ; [Guillot et al, 2020] (94) ; [Abdeljawad et al, 2020] (95) ; [Acar and Feeny, 2018] (96) https://www.indjst.org/ Most of the authors focused upon the design of controllers according to the accurate dynamic model of the flexible arm. Researchers used both the AMM and FEM to model the flexible arm without compromising the accuracy.…”
Section: Inertial Frame Of Referencementioning
confidence: 99%
“…Since measuring the vibrational response is costly and technically challenging, characteristics of blade vibrations have been derived in several simulation studies [5][6][7][8]. Acar and Feeny [5] and Liu et al [6] demonstrated that eigenfrequencies depend on the stiffness of the blade and vary with operational and environmental parameters. Consequently, eigenfrequencies need to be studied under a large variety of conditions.…”
Section: Related Literaturementioning
confidence: 99%
“…In addition, Yoo and Shin [7] showed that centrifugal inertia forces increase with both blade length and rotation speed. In addition, Acar and Feeny [5] studied parametric stiffness effects due to centrifugal and gravitational forces and found that the first eigenfrequency of a 100-m blade varied by up to 1.5% with the rotation angle. In all simulation studies, results varied strongly with parameters and respective models.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…They assumed that the blade under transverse bending and twisting deformation was treated as a uniform straight elastic Euler–Bernoulli beam. The derivation of the energy equations and simplified aerodynamic models for bending and twisting blades have been distributed, and Lagrangian equations have been extended to assumed modal coordinates to derive nonlinear motion equations for bending and twisting blades [ 32 , 33 , 34 , 35 , 36 ]. Meksi et al [ 37 ] derived the equations of motion of functionally graded sandwich plates from Hamilton’s principle based on a new shear deformation plate theory.…”
Section: Introductionmentioning
confidence: 99%